DEVELOPING “PANTOMIM ASYIK ALA KAK PROP” TEXTBOOK AS AN ALTERNATIVE SOURCE OF LEARNING PERFORMING ARTS FOR CHILDREN IN ELEMENTARY SCHOOL - Abdul Amin; Murtono; Irfai Fathurohman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop pantomime textbooks as an alternative source of learning performing arts for children in elementary schools and to determine its feasibility. The research method was R&D referring to Borg and Gall’s theory which was modified into 7 steps. The product of the study was a textbook entitled “Pantomim Asyik ala Kak Prop.” The score of validity test from material experts was 56, with an average of 3.5 and a percentage of 88% in very good category. Then, the score of validity test from a linguist was 27, with an average of 3.4 and a percentage of 84% in very good category. Moreover, the results of limited product trials through the teachers’ response questionnaire found a score of 572, with an average of 3.6 and a percentage of 89.4% in very feasible category. Meanwhile, the students’ response questionnaire found a score of 565, with an average of 3.5 and a percentage of 88.3% in very feasible category. It was concluded that the pantomime textbook was very suitable to be used as an alternative source of learning performing arts for children in elementary schools.